The Effect of Herringbone Technique on Students’ Reading Comprehension through Narrative Text at MTs PAB 1 Helvetia, Medan - Rizky Vita Losi (Jurnal Humaniora Teknologi, 2020)
The Effect of Herringbone Technique on Students’ Reading Comprehension through Narrative Text at MTs PAB 1 Helvetia, Medan Rizky Vita Losi Universitas Pembangunan Panca Budi rizkyvitalosi@pancabudi.ac.id Abstract This research dealt with Herringbone technique which was proposed by Deegan (2006). The aim of this research was to know whether Herringbone technique was effective to be applied on students’ reading comprehension through narrative text. The sample of this research was grade VIII-E students which consisted of 31 students at MTs PAB 1 Helvetia, Medan. The data of this research was students’ reading comprehension score on pre-test and post-test. The data was analyzed by using Paired Sample T-Test formula which was calculated by SPSS 2.2. From the data analysis, it was found that the T-Test value was higher than the T-Table value (10,085 > 2,042). It showed that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It also showed that there was a significance effect after applying Herringbone technique on students’ reading comprehension through narrative text at MTs PAB 1 Helvetia, Medan. Keywords: herringbone technique, students’ reading comprehension, paired sample t-test formula